ANALISIS INFORMASI ANATOMI DAN KUALITAS CITRA PADA SEKUENS T1 SE FAT SATURATION IRISAN SAGITAL OBLIQUE DENGAN VARIASI PHASE OVERSAMPLING PADA PEMERIKSAAN MRI ORBITA - Rachman Kusumadi; Emi Murniati; Siti Daryati (Perhimpunan Radiografer Indonesia (PARI), 2018)
Background: Aliasing artifacts often occur on MRI examinations Orbita sequence T1 SE Fat Saturation sagittal oblique slices. One way to eliminate aliasing artifacts is by setting Phase Oversampling (PO). The purpose of this study was to determine differences in anatomic information and image quality in the T1 SE sequence of oblique sagittal fat saturation slices with PO variations of orbital MRI examinations and to determine the value of PO variations that can produce optimal anatomic information and image quality in the sequences of T1 SE Fat Saturation slices sagittal oblique on Orbita MRI examination. Method: This type of research is quantitative research with an experimental approach. The research subject is Orbita MRI imagery. The research sample consisted of Orbita MRI images obtained from 10 volunteers. Data obtained from SNR and CNR measurements to obtain image quality data, then the image results were assessed by respondents using questionnaires to obtain anatomic information data. The data obtained were analyzed using different tests in the SPSS application. Results: The results showed that there were significant differences in the anatomy of the lens with aliasing artifact variations in PO 13%, while PO 52% and 91% had no aliasing artifacts. Optic nerve anatomy has a clear and well-defined image at PO 91% compared to PO 13% and 52%. Friedman test results on anatomic information on the anatomy of the Lens, superior Muscle rectus, and Optic nerve are significant with p-value <0.05, meaning there are differences in anatomic information with variations in PO. Friedman anatomy test results of Retro orbit, Muscle rectus inferior, and Vitreous are significant with p-value> 0.05, meaning there is no difference in anatomic information with variations in PO. Furthermore, the results of the study showed that there were differences in image quality (SNR and CNR) against PO variations with significance values ​​(p <0.05). Conclusion : Based on the calculation of the mean rank Friedman test shows that the more the PO value increases, the quality (SNR and CNR values) increases. The PO 91% setting produces a more optimal image.